Atrial Arrhythmias in Obstructive Sleep Apnea: Underlying Mechanisms and Implications in the Clinical Setting. (3rd April 2013) - Filgueiras-Rama, David; Arias, Miguel A.; Iniesta, Ángel; Armada, Eduardo; Merino, José L.; Peinado, Rafael; López-Sendón, J. L.
Abstract : Obstructive sleep apnea (OSA) is a common disorder characterized by repetitive interruption of ventilation during sleep caused by recurrent upper airway collapse, which leads to intermittent hypoxia. The disorder is commonly undiagnosed despite its relationship with substantial cardiovascular morbidity and mortality. Moreover, the effects of the disorder appear to be particularly dangerous in young subjects. In the last decade, substantial clinical evidence has identified OSA as independent risk factor for both bradyarrhythmias and tachyarrhythmias. To date the mechanisms leading to such arrhythmias have not been completely understood. However, recent data from animal models and new molecular analyses have increased our knowledge of the field, which might lead to future improvement in current therapeutic strategies mainly based on continuous positive airway pressure. This paper aims at providing readers a brief and specific revision of current knowledge about the mechanisms underlying atrial arrhythmias in OSA and their clinical and therapeutic implications.